An Innovative Research on People’s Mediation in Social Governance - Wenhui Meng (Law and Economy, 2023)
This paper aims to explore the innovative practice and development trend of people’s mediation in social governance. By expounding the basic concepts and principles of people’s mediation, this paper reveals the important role of people’s mediation in solving social contradictions and disputes. At the same time, it analyzes the role of policy support and legal guarantee in promoting people’s mediation, as well as innovative practices in mediation organization construction, mediation methods and technological innovation, and mediation mechanism optimization. Finally, this paper looks forward to the development trend of people’s mediation in social governance and puts forward some suggestions and countermeasures such as the promotion of system innovation and technology application, as well as the importance of legal reform and personnel training. The innovative research of people’s mediation in social governance is a subject with important theoretical and practical significance, which plays a positive role in promoting social harmony and stability.